Insertion experience of women and health care professionals in the Kyleena® Satisfaction Study. (3rd May 2020) - Beckert, Vita; Aqua, Keith; Bechtel, Christoph; Cornago, Sonia; Kallner, Helena Kopp; Schulze, Andrea; Parashar, Pooja; Waddington, Ashley; Donders, Gilbert
Abstract: Purpose: The Kyleena ® Satisfaction Study (KYSS) is a prospective, observational study conducted to assess satisfaction with LNG-IUS 12 (Kyleena ® ) in clinical practice and aims to provide adequate information for counselling women on what to expect regarding insertion and satisfaction. Materials and methods: Women deciding to use LNG-IUS 12 during routine counselling were informed of the study and provided informed consent. A baseline analysis was conducted to evaluate demographics, ease of insertion assessed by investigators, pain at insertion rated by women, additional interventions for insertion, and adverse events. Results: 1, 110 women (536 parous, 574 nulliparous) had an insertion attempt and were included. Insertion was rated as easy in 494 (92.2%) parous and 516 (89.9%) nulliparous women. Pain was assessed as none or mild by 475 (88.6%) parous and 387 (67.4%) nulliparous women. Additional interventions were not required for most insertions (705; 63.6%). Overall 111 (10.0%) women reported adverse events at the time of baseline analysis. Conclusions: This analysis demonstrates that LNG-IUS 12 insertion is easy and associated with no or mild pain in most women. Additional interventions for insertion are not required in most cases. After 3 months, the number of adverse events is low. Implications: The present baseline analysis of the Kyleena ® Satisfaction Study (KYSS) demonstrates that most women rate insertion pain of LNG-IUS 12 as none or mild and clinicians consider insertion easy in the majority of cases.